Character Value in Kampong Sala Legend and its Relevancy as Teaching Materials at School - Hetami, Fatma; Sukoyo, Joko; Widodo, Widodo (Language Circle: Journal of Language and Literature, 2018)
The research is aimed at preserving the story of Kota Sala Legend. It used qualitative approach. The data were derived from caretakers, the elderly, the artists from Surakarta Palace, and the public figures, as well as from books and articles by using documentation and interview techniques. The data were analyzed by using qualitative descriptive method into several steps as the following: (1) Conducting interview and observing the documents, (2) Collecting and arranging the data into a complete story, (3) Analyzing its character values, and (4) Analyzing its relevance as a teaching material. The results indicate that (1) the oral tradition of Kampong Sala Legend can be documented into a pictorial story book in three languages: Javanese, Indonesian, and English; (2) The story consists of character values such as religious, honest, discipline, hard-working, creative, solicitous, and responsible; (3) The story is very relevantly used as teaching materials at school especially in the subject of Bahasa Jawa and Bahasa Indonesia.